Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

A Pharmacokinetic Analysis of Hemodialysis for Metformin-Associated Lactic Acidosis - Stephen A. Harding; Rana Biary; Robert S. Hoffman; Mark K. Su; Mary Ann Howland (Journal of Medical Toxicology, 2021)

Tert-butyldimethylsilyl chitosan synthesis and characterization by analytical ultracentrifugation, for archaeological wood conservation - Jennifer M. K. Wakefield; Susan Braovac; Hartmut Kutzke; Robert A. Stockman; Stephen E. Harding (European Biophysics Journal, 2020)
The Oseberg ship is one of the most important archaeological testimonies of the Vikings. After excavation in 1904, the wooden gravegoods were conserved using alum salts. This resulted in extreme degradation of a number of the objects a hundred years later through acid depolymerisation of cellulose and lignin. The fragile condition of the artefacts requires a reconsolidation which has to be done avoiding water as solvent. We synthesized tert- butyldimethylsilyl (TBDMS) chitosan which is soluble in a 50:50 solution of ethyl acetate and toluene. Measurement of its molecular weight, to anticipate its penetration, provided a challenge as the density difference of the polymer and solvent was too small to provide adequate solute redistribution under a centrifugal field, so a two-stage process was implemented (i) determination of the weight-average molar mass of the aqueous soluble activated precursor, chitosan mesylate, M w,mc using sedimentation equilibrium with the SEDFIT-MSTAR algorithm, and determination of the degree of polymerisation DP ; (ii) measurement of the average degree of substitution DS TBDMS of the TBDMS group on each chitosan monosaccharide monomer unit using NMR, to augment the M w,mc value to give the molar mass of the TBDMS-chitosan. For the preparation, we find M w = 9.8 kg·mol −1 , which is within the acceptable limit for penetration and consolidation of degraded wood. Future work will test this on archaeological wood from different sources.

Production of membrane proteins for characterisation of their pheromone-sensing and antimicrobial resistance functions - Aalishaa A. Azam; Jean M. Kinder; G. Nasir Khan; Ade Alase; Pikyee Ma; Yang Liu; James R. Ault; Peter J. F. Henderson; Babur Z. Chowdhry; Bruce D. Alexander; Stephen E. Harding; Mary K. Phillips-Jones (European Biophysics Journal, 2018)

Controlled depolymerisation assessed by analytical ultracentrifugation of low molecular weight chitosan for use in archaeological conservation - Jennifer M. K. Wakefield; Richard B. Gillis; Gary G. Adams; Caitlin M. A. McQueen; Stephen E. Harding (European Biophysics Journal, 2018)

Capital and income breeding: the role of food supply - Philip A. Stephens; Alasdair I. Houston; Karin C. Harding; Ian L. Boyd; John M. McNamara (Ecology, 2014)
An aspect of life history that has seen increasing attention in recent years is that of strategies for financing the costs of offspring production. These strategies are often described by a continuum ranging from capital breeding, in which costs are met purely from endogenous reserves, to income breeding, in which costs are met purely from concurrent intake. A variety of factors that might drive strategies toward a given point on the capital–income continuum has been reviewed, and assessed using analytical models. However, aspects of food supply, including seasonality and unpredictability, have often been cited as important drivers of capital and income breeding, but are difficult to assess using analytical models. Consequently, we used dynamic programming to assess the role of the food supply in shaping offspring provisioning strategies. Our model is parameterized for a pinniped (one taxon remarkable for the range of offspring‐provisioning strategies that it illustrates). We show that increased food availability, increased seasonality, and, to a lesser extent, increased unpredictability can all favor the emergence of capital breeding. In terms of the conversion of energy into offspring growth, the shorter periods of care associated with capital breeding are considerably more energetically efficient than income breeding, because shorter periods of care are associated with a higher ratio of energy put into offspring growth to energy spent on parent and offspring maintenance metabolism. Moreover, no clear costs are currently associated with capital accumulation in pinnipeds. This contrasts with general assumptions about endotherms, which suggest that income breeding will usually be preferred. Our model emphasizes the role of seasonally high abundances of food in enabling mothers to pursue an energetically efficient capital‐breeding strategy. We discuss the importance of offspring development for dictating strategies for financing offspring production.

The Hypoglycemic Effect of Pumpkin Seeds, Trigonelline (TRG), Nicotinic Acid (NA), and D-Chiro-inositol (DCI) in Controlling Glycemic Levels in Diabetes Mellitus - Gary G. Adams; Shahwar Imran; Sheng Wang; Abubaker Mohammad; M. Samil Kok; David A. Gray; Guy A. Channell; Stephen E. Harding (Critical Reviews in Food Science and Nutrition, 2014)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Coadministration of intravenous nicotine and oral alcohol in rats - A. D. Lê; Steven Lo; Stephen Harding; Walter Juzytsch; Peter W. Marinelli; Douglas Funk (Psychopharmacology, 2010)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

The CRF1 receptor antagonist antalarmin attenuates yohimbine-induced increases in operant alcohol self-administration and reinstatement of alcohol seeking in rats - Peter W. Marinelli; Douglas Funk; Walter Juzytsch; Stephen Harding; Kenner C. Rice; Yavin Shaham; A. D. Lê (Psychopharmacology, 2007)

Trp203 mutation in GroEL promotes a self-association reaction: a hydrodynamic study - Chris Walters; Anthony Clarke; Matthew J. Cliff; Peter A. Lund; Stephen E. Harding (European Biophysics Journal, 2000)

Hydrodynamic properties of mucins secreted by primary cultures of Guinea-pig tracheal epithelial cells: determination of diffusion coefficients by analytical ultracentrifugation and kinetic analysis of mucus gel hydration and dissolution - Sara Dodd; Graham A. Place; R. L. Hall; Stephen E. Harding (European Biophysics Journal, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

The reduction in alcohol intake by the 5-HT 1A agonist 8-OH DPAT and its attenuation by the α 2 adrenergic antagonist idazoxan correlates with blood glucose levels - Larry A. Grupp; Vicky Lau; Stephen Harding (Psychopharmacology, 1997)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)